Indicateurs des impacts du développement sur l'environnement : une comparaison Afrique - Europe - Bruno Kestemont; L. Frendo; Edwin Zaccai (VertigO)
We calculate and present in this paper quantitative data about the impact on the environment for a cluster of Western European countries and a cluster of Western African countries. Six major topics are considered: (1) land use, (2) modification of atmospheric composition, (3) decline in water resources, (4) change in nitrogen cycle, (5) loss of biodiversity, (6) exploitation of fisheries. We show how the choice of indicators may strongly influence the results within these areas. We find that the relative impacts of African countries show higher than those of European countries, taking into account their specific economic levels. We conclude with several explanations of this major result, which all require an increased consideration of sustainable development objectives in Africa.